ASSOCIATION OF PATHOLOGICAL ACTIVITY OF ORAL CANDIDA AND DENTURE WEARING HABIT IN DENTURE WEARERS - Chughtai, Muhammad Ali; Naseer, Amjid; Ghani, Fazal; Khan, Mohammad Sartaj (Journal of Postgraduate Medical Institute, 2012)
Objective: To assess the effect of denture wearing on oral candidal activity through candida selectivemedium inoculated with standardized dilution salivary samples obtained from denture wearers. Methodology: A cross sectional, comparative study during March-September 2007 was conducted atKhyber College of Dentistry Peshawar. Using a structured proforma, data were collected from 50 subjects(50 Denture wearers). Stimulated salivary samples were collected from each subject. One ml of standarddilution saliva was mixed with 4ml sterile liquid candida –selective medium. The extent of candida activitywas then determined, biochemically, through change in pH of the medium 24hrs after inoculation andincubation at 37 C. Results: Pathological candidal activity was seen in denture wearers. However, the association between thedenture wearing habit and candidal activity was found significant, meaning that continuous denturewearing always showed a high pH change (t- value of 0.01) and mean pH decrease of 2.2 in continuousdenture wearers as compare to 1.6 in only day time wearers. Beside this denture plaque score, type ofdentures and denture hygiene maintenance was found to have insignificant association with the candidalactivity. Conclusion: Within the limits of this study, denture wearing significantly enhanced the pathogenic activityof oral candida. The importance of rest to denture supporting tissue is re-emphasized.